Bacterial communities in soils as indicators of the potential of syenite as an agromineral - Baptista, Joana de Carvalho; Gray, Neil Duncan; Tarumoto, Miriam Büchler [UNESP]; Singleton, Ian; McCann, Clare Maria; Manning, David Andrew Charles (FapUNIFESP (SciELO), 2022)
The objective of this work was to identify microbial communities associated with the surfaces of alkali feldspars and to determine whether these microbes might be involved in the weathering of these rocks for agronomic benefit. Samples were taken from weathering profiles and soils developed on a syenite, considered as a raw material for agromineral production, located in the municipality of Triunfo, in the state of Pernambuco, Brazil. Molecular microbiological techniques (qPCR and 16S rRNA gene sequencing) were used, and data were interpreted by the analysis of variance, hierarchical cluster analysis, and principal coordinates analysis. In addition, scanning electron microscopy was used to image mineral surfaces. Similar bacterial communities were observed in all samples, showing that the bacteria found in soil are present at the earliest stages of rock weathering and are available to play a role in nutrient release. In particular, Actinobacteria and, within this phylum, Actinomycetales were proportionally more abundant than other taxa in rock-dominated soil samples, i.e., in thin soils on or between fractured or broken syenite. The analysis of rock dust used as a remineralizer, crushed with no further treatment, shows that Actinobacteria play a role in the early stages of weathering of feldspar-bearing rocks
Comunidades bacterianas associadas aos processos intemperizados como indicadores do potencial do sienito como agromineral
Keywords: Actinobacteria; Actinomycetales; Agromineral; Bacteria; Microbial community; Syenite